The Impact of Tourism on A Country's Economy - Xojamuratova Shaxnoza Almuratovna (International Journal Of Management And Economics Fundamental, 2025)
Tourism is widely recognized as a key driver of economic growth and development in many countries. This article explores the multifaceted economic impact of tourism, ranging from employment generation and foreign exchange earnings to infrastructure development and regional economic integration. With global tourism contributing over 9% to the world's GDP before the COVID-19 pandemic, its role in economic recovery and diversification has become more vital than ever. The article examines the direct, indirect, and induced effects of tourism, supported by global statistics and national case studies, and also addresses the potential challenges such as over-tourism and seasonal fluctuations. Ultimately, tourism emerges as a powerful economic tool, provided it is managed sustainably and inclusively.